2000
DOI: 10.1021/ic000366c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of One-, Two-, and Three-Dimensional Open-Framework Zinc Phosphates in the Presence of a Tetramine

Abstract: Five new open-framework zinc phosphates, encompassing the entire hierarchy of open-framework structures, have been synthesized hydrothermally in the presence of triethylenetetramine. The structures include one-dimensional ladders, two-dimensional layers, and three-dimensional structures as well as a zinc phosphate where the amine acts as a ligand. [C6N4H22]0.5[Zn(HPO4)2] (I): monoclinic, space group P2(1)/c (no. 14), a = 5.2677(1) A, b = 13.3025(1) A, c = 14.7833(1) A, beta = 96.049 degrees, Z = 4. [C6N4H22]0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 26 publications
(50 reference statements)
8
79
0
Order By: Relevance
“…The synthesis and structures of these new zinc phosphates have been reported recently by us (10). The powder X-ray di!raction (XRD) pattern (Siemen's D5000, CuK , "1.5418 A s , graphite monochromator, Ni "lter) of the powdered single crystals indicated that the product was a new material; the pattern was entirely consistent with the structure determined by single-crystal X-ray di!raction.…”
Section: Methodssupporting
confidence: 73%
“…The synthesis and structures of these new zinc phosphates have been reported recently by us (10). The powder X-ray di!raction (XRD) pattern (Siemen's D5000, CuK , "1.5418 A s , graphite monochromator, Ni "lter) of the powdered single crystals indicated that the product was a new material; the pattern was entirely consistent with the structure determined by single-crystal X-ray di!raction.…”
Section: Methodssupporting
confidence: 73%
“…Over the past couple of decades, a considerable number of metal phosphates/phosphites with open molecular architectures have also been synthesized incorporating organic units (see, for example: Jiang et al, 2001) and ionic liquids (Cooper et al, 2004) as structure-directing agents, often under hydrothermal or solvothermal conditions. One of the best known families of this type consists of zinc phosphate structures; individual materials of this type can exist as one dimensional (chain and ladder), two dimensional (layer) and three dimensional framework arrangements (Choudhury et al, 2000).…”
mentioning
confidence: 99%
“…Studies have shown that the important role of host-guest charge matching between the inorganic frameworks and the organic amines makes linear polyamines the preferred candidates for the structure-directing agents to form the higher negative charge framework of zinc and cobalt phosphates (Bu et al, 1997(Bu et al, , 1998Feng et al, 1997). Moreover, diethylenetriamine (DETA), triethylenetetramine (TETA) and tetraethylenepentamine (TEPA) become typical amines and have directed the formation of a large number of open-framework structures of zinc (or cobalt) phosphates by varying their concentrations accompanying with the changes in inorganic compositions (Choudhury et al, 2000). Recently, a new synthesis route involving alkylformamide as a template precursors has been reported (Lakiss et al, 2005;Vidal et al, 2000).…”
Section: Introductionmentioning
confidence: 99%